The Practice of Teaching Arabic Speaking Skills at Sunan Drajat University - Widodo, Arif (Funun Arabiyyah: Journal of Arabic Education and Literature, 2025)
This study aims to describe the implementation of mahārah kalām learning at UNSUDA Lamongan and to analyze its effectiveness in improving students’ speaking competence. Using a qualitative descriptive approach, data were collected through observation, interviews, and documentation. The findings show that the implementation of mahārah kalām learning falls into the category of highly effective. This is evidenced by several indicators: (1) students’ motivation level reached 80%; (2) activeness in attending lectures was 90%; (3) students’ positive evaluation of interactive materials reached 90%; and (4) intensive question–answer practice occurred throughout the learning process. These results indicate that the applied instructional strategies successfully encouraged active participation and enhanced students’ oral communication skills in Arabic. The study recommends strengthening continuous speaking practice programs to sustain and improve these achievements.